Gas emission through coal particles using instantaneous gas diffusion coefficients: experimental and modelling study. (3rd October 2019) - Shi, Guangshan; Hao, Tianxuan; Bai, Pengfei; Zhang, Yugui
Similarity theory and the second law of diffusion were used to develop a diffusion model to accurately characterise the behaviour of gas emissions from coal particles. A method for calculating instantaneous diffusion coefficients, D ( t ), was established. These were incorporated into the diffusion equation and its analytical solution obtained via separation of variables. The results indicated that changes of D ( t ) as a function of time were described by a power function. The model accurately characterises the entire process of gas emission from coal particles and reflects the complexities of pore size. It provides a new calculation method and theoretical reference for determination and prediction of parameters for gas emission from coal seams. [Received: August 10, 2017; Accepted: January 9, 2018]